Convergindo na divergência: emersão, atuação e governança multinível da U.S. Climate Alliance no governo Donald Trump - Silva, Wilker Jeymisson Gomes da (2021)
The participation of subnational governments on global agendas is a recurrent debate, including when it comes to coping with climate change. The localization of this agenda, based on the singularities of local and regional realities, makes it necessary to think about alternatives to minimize the limitations of individual action. The union of local governments has been an alternative used to coordinate actions and seek common interests, an artifice used by several U.S. state governments in response to the 2017 withdrawal of the United States of America from the Paris Agreement on climate change. The bipartisan organization United States Climate Alliance, committed to continuing on the path to reach the Paris Agreement goals, appears as a way to align the local interests of the members with the global aspirations for climate action, promising to lead the internalization of the agenda due to the lack of action left by the federal level. Considering the divergence of agendas between the two actors listed in the investigation, this research was based on the following question: how is the relationship between the coalition and the federal level? Starting from the local level to act on a global agenda, a scenario that is still considered to be the predominant participation of States, this study considered the importance of understanding elements related to multilevel governance and horizontal and vertical collaboration in the performance of this alliance of subnational entities. Thus through analytical-descriptive research, based on the case study method, investigates how the multilevel performance of the US Climate Alliance takes place, with an emphasis on the analysis of the existing collaboration between climate policies at the level of the US Climate Alliance and the US federal level during the term of President Donald Trump (2017-2021). As a result, it was found a low participation of the federal level in the actions of the alliance, concluding that there is no vertical collaboration, although there is considerable collaboration at the horizontal level. Furthermore,the actions of the coalition occurred predominantly within the US domestic scenario.